Elevated peripheral inflammation is associated with attenuated striatal reward anticipation in major depressive disorder - Burrows, Kaiping (Brain Behav Immun, 2021)
BACKGROUND: Major depressive disorder (MDD) is the leading cause of years lived with disability worldwide, and up to 40% of individuals with MDD do not respond to current treatments. Studies suggest that peripheral inflammation plays an important role in the striatal mesolimbic dopamine pathway and corticostriatal reward circuitry in MDD. Although MDD patients show blunted striatal responses to reward, the link between degree of inflammation and attenuation of reward processing is unclear. We investigated whether MDD patients with elevated peripheral inflammation exhibit attenuated reward responses to enhance our understanding of MDD pathophysiology and develop more effective treatments for current non-responders. METHODS: MDD subjects varying on serum C-reactive protein (CRP) concentrations (MDD-High CRP, > 3mg/L, n=44; MDD-Low CRP, < 3mg/L, n=44) and healthy comparisons (HC, n=44) completed a monetary incentive delay (MID) task and provided blood samples to measure inflammation-related markers. MDD-High and MDD-Low were propensity score-matched on age, sex, body mass index (BMI), smoking status, exercise and MID task head motion. Percent change in blood oxygen level-dependent (BOLD) signal during anticipation of wins and losses was extracted from bilateral nucleus accumbens, dorsal caudate and dorsolateral putamen regions of interest (ROIs). A linear mixed-effects model was used to test group (MDD-High, MDD-Low and HC), condition (large-win, small-win and no win), and their interaction for these ROIs as well as whole-brain voxelwise data. Analyses also tested group differences in inflammatory mediators. Correlations were used to explore the relationship between inflammatory mediators and brain regions showing differences between MDD-High and MDD-Low. RESULTS: MDD-High exhibited: (a) lower BOLD signal change in dorsal caudate, thalamus, left insula and left precuneus during anticipation of small wins than MDD-Low; and (b) higher serum soluble intercellular adhesion molecule 1 (sICAM-1) and interleukin 6 (IL-6) concentrations than MDD-Low and HC. MDD as a whole, regardless of CRP-based inflammation, exhibited: (a) lower precuneus BOLD signal change to large wins than HC; and (b) higher Interleukin 1 receptor antagonist (IL-1ra), macrophage-derived chemokine (MDC) and macrophage inflammatory protein-1 alpha (MIP-1α) concentrations than HC. Higher serum sICAM-1 concentrations were associated with lower caudate BOLD signal change to small wins only within the MDD-High group. CONCLUSION: Within MDD patients, high inflammation (CRP, sICAM-1) was linked to reduced striatal activation recruited to discriminate intermediate reward magnitudes. These findings support an association between levels of peripheral inflammation and the degree of reward-related activation in individuals with MDD. REGISTRATION OF CLINICAL TRIALS: The ClinicalTrials.gov identifier for the clinical protocol associated with data published in this current paper is NCT02450240, “Latent Structure of Multi-level Assessments and Predictors of Outcomes in Psychiatric Disorders.”